KISHVA AMBIGAPATHY: DISCOVERING SMALL OPPORTUNITIES HAVE MADE ME INTO A GLOBAL LEADER - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 25 March 2016 – Small opportunities would usually signify the beginning of greater achievements, as highlighted by Kishva Ambigapathy, who used to be a school librarian and now is back at home in Malaysia to meet with the Youth Parliament of Malaysia and the Youth Association of Malaysia.